Enhancement of n-type conductivity of hexagonal boron nitride films by in-situ co-doping of silicon and oxygen. (21st September 2022) - Kang, Yun; Chen, Le; Liu, Caiyun; Tang, Xuemei; Zhu, Xingrui; Gao, Wei; Yin, Hong
Abstract: Effective doping of ultra-wide band gap semiconductors is of crucial importance, yet, remains challenging. Here, we report the enhancement of n -type conductivity of nanocrystalline hexagonal boron nitride ( h -BN) films with simultaneous incorporation of Si and O while deposition by radio frequency magnetron sputtering method. The resultant h -BN films are of ∼50 nm in thickness, containing nitrogen vacancy (VN ) defects. Incorporation of O together with Si results in effective healing of VN defects and significantly reduces electric resistivity in h -BN thin films. X-ray photoelectron spectroscopy results reveal that under B-rich condition, the substitutional O in VN bonding with B leads to the formation of Si–N, which thus plays an important role to the n -type conductivity in h -BN films. The temperature dependent electrical resistivity measurements of the Si/O co-doped h -BN films reveal two donor levels of 130 and 520 meV at room temperature and higher temperatures, respectively. The n-h -BN/ p -Si heterojunctions demonstrate apparent rectification characteristics at room temperature, where the tunneling behavior dominates throughout the injection regimes due to the effective carrier doping. This work proposes an effective approach to enhance the n -type conductivity of h -BN thin films for future applications in electronics, optoelectronics and photovoltaics.